Remdesivir (GS-5734) Impedes Enterovirus Replication Through Viral RNA Synthesis Inhibition - Ye, Wei; Yao, Min; Dong, Yangchao; Ye, Chuantao; Wang, Dan; Liu, He; Ma, Hongwei; Zhang, Hui; Qi, Libin; Yang, Yuewu; Wang, Yuan; Zhang, Liang; et al. (Frontiers in Microbiology, 2020)
Human enteroviruses are responsible for diverse diseases, from mild respiratory symptoms to fatal neurological complications. Currently, no registered antivirals have been approved for clinical therapy. Thus, a therapeutic agent for enterovirus-related disease is urgently needed. Remdesivir (GS-5734) is a novel monophosphoramidate adenosine analog prodrug that exhibits potent antiviral activity against diverse RNA virus families, including positive-sense Coronaviridae and Flaviviridae and negative-sense Filoviridae, Paramyxoviridae, and Pneumoviridae. Currently, remdesivir is under phase 3 clinical development for disease COVID-19 treatment. Here, we tested remdesivir efficacy against enterovirus 71 (EV71) and found that remdesivir impeded both EV71 viral RNA (vRNA) and complementary (cRNA) synthesis, indicating that EV71 replication is inhibited by the triphosphate (TP) form of remdesivir. Moreover, remdesivir showed potent antiviral activity against diverse enteroviruses. These data extend the remdesivir antiviral activity to enteroviruses and indicate that remdesivir is a promising antiviral treatment for EV71 and other enterovirus infections.